STRATEGIC MANAGEMENT OF THE ECONOMIC SECURITY OF THE AGRICULTURAL ENTERPRISE IN THE BUSINESS ENVIRONMENT - POMAZ, Oleksandr; KRYVCHUN, Rostyslav; PRYIMA, Valerii; LAZORENKO, Vitalii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the main components of the marketing strategy of agrarian enterprises in a dynamic business environment. Considered interpretations of the concept of "marketing strategy". It has been established that the marketing strategy is a tool for achieving the marketing goals of an agricultural enterprise. The main tasks in the development of a marketing strategy have been studied. The main directions of the marketing strategy are highlighted. It has been proven that the main goal of the marketing strategy of agricultural enterprises is to ensure their stability, long-term development and obtain maximum profit from economic activity. The process of forming a marketing strategy is substantiated and analyzed, the main theoretical aspects of a marketing strategy and its main stages are outlined. The work also considers modern marketing strategy tools that can be effective for increasing the profitability of agricultural enterprises. On the basis of the analysis, optimal methods of increasing competitiveness and expanding product sales markets are determined.The formation of a marketing strategy is one of the key stages of the activity of any enterprise, which allows you to direct its resources to achieve business goals through effective interaction with the market and consumers. The marketing strategy depends on how the company will position its goods or services on the market, which markets and segments will be prioritized, as well as which marketing tools will be used to achieve results. A marketing strategy is a plan of action aimed at promoting a product or service to achieve business goals. It includes defining the target audience, analyzing competitors, choosing promotion channels, as well as defining methods and tools for achieving goals.
Keywords: marketing strategy; enterprise strategy; agricultural enterprises; dynamic business environment; long-term development